Aplikasi Beberapa Macam Komposisi Pupuk Organik Cair (POC) Pada Pertumbuhan dan Hasil Tanaman Sorgum - Rosita Shofi; Nurhidayati Nurhidayati; Anis Rosyidah; Tarbiyatul Munawwarah (Universitas Islam Malang, 2022)
The need for sorghum from time to time is increasing for various purposes, including for feed, food and industrial materials. On the other hand, sorghum production is still low. The development of sorghum cultivation is directed at land with low fertility levels such as Ultisol soil. Therefore, it is necessary to apply environmentally friendly cultivation technology. The purpose of this study was to explain the effect of application of various Liquid Organic Fertilizer (LOF) compositions and their concentrations on the growth and yield of sorghum. This research was conducted at the Agricultural Technology Research and Development Installation (IP2TP) Samboja, East Kalimantan starting in December 2020 until March 2021. This study used a Split Plot Design where the main plot was a type of LOF composition consisting of 5 levels and sub-plots is the concentration of LOF consisting of 3 levels with the frequency of spraying LOF 3 times in one planting period (10 days interval). The results of this study showed that the combination of various LOF compositions and their concentrations did not have a significant interaction effect on the growth and yield of sorghum plants. The best composition of was the mixture of goat urine, amino acids and bioactivators, with plant height growth at 53 DAP of 182.81 cm, fresh weight of leaves and stems of 19558.07 grams/plot equivalent to 48.90 tons/ha and dry weight of seeds 3278.53 grams/plot. equivalent to 8.20 tons/ha dry weight of seeds.